Awareness about Expressed Breast Milk Storage and Feeding Among Nurses in a Tertiary Care Hospital of Coastal South India - Maadtha, Saanchia Andrea; Amreen, Shahla; Rao S, Suchetha (National Journal of Community Medicine, 2021)
Introduction: Health personnel play a vital role in feeding baby with stored human milk and in educating mothers about expressed breast milk (EBM). Studies assessing nurses’ knowledge about EBM are limited. We aimed to study the awareness about EBM storage and preparation for feeding among pediatric nurses. Methodology: A cross sectional study was carried out in tertiary care hospitals of South India. Participants answered the pretested questionnaire. Mean awareness score percentages of the participants was calculated, and compared for age, years of experience and place of work. Results: Study enrolled 105 paediatric nurses with mean age of 33.13 ±12.05 years. Majority of participants knew the reason for expressing breast milk, how to express breast milk. Regarding the storage temperature of EBM, less than 50 % of the nurses were aware and 34.3% of nurses knew the preparation for feeding. The mean awareness score percentage was 65.71 ±16.64. Age group >40 years, neonatal intensive care unit nurses and work experience >10 years had significant relation to awareness scores. Conclusion: Knowledge of nurses regarding reasons for and technique of expressing breast milk, methods of storing of EBM was good. Knowledge about storage temperatures and preparation for feeding was inadequate. Age group >40 years, neonatal intensive care unit as place of work and more than 10 years’ work experience related to the knowledge.